Indonesia's financial markets and monetary policy dynamics amid the Covid-19 pandemic - Eric Alexander Sugandi (Asian Development Bank Institute (ADBI), 2020)
This paper is based on a study that examines the impact of the Covid-19 pandemic on Indonesia's financial markets and monetary policy dynamics. The study explores five types of financial market in Indonesia: (1) the Indonesian rupiah (IDR) interbank money market; (2) the US Dollar (USD) interbank money market; (3) government conventional bond (SUN) markets; (4) the stock market; and (5) the USD/IDR spot market. It examines Bank Indonesia's (BI) three types of monetary policy instrument: (1) BI seven-day reverse repo rate; (2) minimum reserve requirement ratios; and (3) BI's monetary operations. The study finds that the Covid-19 pandemic causes different impacts of particular monetary policy instruments on Indonesia's financial markets during the pandemic compared to those in the non-pandemic period.
Keywords: E58; G10; 330; Covid-19; monetary policy; Indonesia's financial markets; Bank Indonesia